2018
DOI: 10.3390/nu10121927
|View full text |Cite
|
Sign up to set email alerts
|

Gluten Immunogenic Peptides as Standard for the Evaluation of Potential Harmful Prolamin Content in Food and Human Specimen

Abstract: Gluten is a complex mixture of storage proteins in cereals like wheat, barley, and rye. Prolamins are the main components of gluten. Their high content in proline and glutamine makes them water-insoluble and difficult to digest in the gastrointestinal tract. Partial digestion generates peptide sequences which trigger immune responses in celiac and gluten-sensitive patients. Gluten detection in food is challenging because of the diversity, in various food matrices, of protein proportions or modifications and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 107 publications
0
38
0
Order By: Relevance
“…34,69 Two peptides that have attracted most attention and remain intact in the digestive process are the 33-mer (p55-87) and the 25-mer (p31-55) located in the αgliadins encoded by the Gli-D2 locus on chromosome 6D. 73,74 Of these two peptides, the 33-mer is the most digestion-resistant peptide with high immunogenic properties (contains DQ2.5-glia-α1a, DQ2.5-glia-α1b, and DQ2.5-glia-α2 epitopes). 75,76 During or after absorption of partially digested gliadin peptides into the lamina propria, specific glutamine residues of the 33-mer peptide are susceptible to pH-dependent transamidation (covalent cross-linking to free amines, for example, lysine residues submit your manuscript | www.dovepress.com…”
Section: Gluten Protein and The Pathogenesis Of Various Grds Celiac Dmentioning
confidence: 99%
“…34,69 Two peptides that have attracted most attention and remain intact in the digestive process are the 33-mer (p55-87) and the 25-mer (p31-55) located in the αgliadins encoded by the Gli-D2 locus on chromosome 6D. 73,74 Of these two peptides, the 33-mer is the most digestion-resistant peptide with high immunogenic properties (contains DQ2.5-glia-α1a, DQ2.5-glia-α1b, and DQ2.5-glia-α2 epitopes). 75,76 During or after absorption of partially digested gliadin peptides into the lamina propria, specific glutamine residues of the 33-mer peptide are susceptible to pH-dependent transamidation (covalent cross-linking to free amines, for example, lysine residues submit your manuscript | www.dovepress.com…”
Section: Gluten Protein and The Pathogenesis Of Various Grds Celiac Dmentioning
confidence: 99%
“…Although growth and gliadin hydrolysis plating approach is an appropriate initial step for the selection of microorganisms capable of utilizing gluten, highly active gluten-degrading enzymes nor specificities of interest targeting immunogenic domains are not necessarily produced and exhibit by the isolated strains [34]. Therefore, further evaluation was required to check the reduction of gluten immunogenic peptides (GIP) by the selected strain since the detection of GIP has been proposed as the analytical standard reference for the determination of the immunopathological risk of gluten exposure in gluten-related diseases [35].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have demonstrated that the G12 moAb specifically recognizes the immunoreactive peptides in those gluten proteins that have a reported characterization of the consistency with ex-vivo -quantified immunogenicity with T-cells from celiac individuals [3539]. To monitor GIP hydrolysis, microbial encapsulation in monodisperse hydrogel gliadin microspheres was performed with Cellena Flow Focusing technology (Ingeniatrics).…”
Section: Resultsmentioning
confidence: 99%
“…GIP, analyzed in stools and urine by using commercial ELISAs (monoclonal antibodies G12 and/or A1), have been proposed as new non-invasive biomarkers to detect gluten intake and to verify GFD compliance in patients with CD [45,46,49,[80][81][82][83][84][85]. GIP are resistant to gastrointestinal digestion and responsible for immunogenic reactions in the T cells of patients with CD [83]. Unlike traditional methods for monitoring GFD adherence, which only evaluate the consequences of GFD transgressions, this non-invasive method enables a direct and quantitative assessment of gluten exposure.…”
Section: Stools and Urine Testingmentioning
confidence: 99%